High Solid Dispersions - Cloitre, Michel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
From Polymers to Colloids: Engineering the Dynamic Properties of Hairy Particles, by D. Vlassopoulos and G. Fytas * Nonlinear Rheological Properties of Dense Colloidal Dispersions Close to a Glass Transition Under Steady Shear, by M. Fuchs * Micromechanics of Soft Particle Glasses, by R. T. Bonnecaze and M. Cloitre * Quantitative Imaging of Concentrated Suspensions Under Flow, by L. Isa, R. Besseling, A. B. Schofield and W. C. K. Poon * Soft and Wet Materials: From Hydrogels to Biotissues, by J. P. Gong and Y. Osada
From Polymers to Colloids: Engineering the Dynamic Properties of Hairy Particles -- Nonlinear Rheological Properties of Dense Colloidal Dispersions Close to a Glass Transition Under Steady Shear -- Micromechanics of Soft Particle Glasses -- Quantitative Imaging of Concentrated Suspensions Under Flow -- Soft and Wet Materials: From Hydrogels to Biotissues.
Keywords: Chemistry; Polymers; Biomaterials; Chemistry; Polymer Sciences; Soft and Granular Matter, Complex Fluids and Microfluidics; Biomaterials